2022
DOI: 10.1210/clinem/dgac395
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity Status, Trajectories, and Earlier Puberty Onset: Results From a Longitudinal Cohort Study

Abstract: Context Adiposity is associated with earlier puberty onset in girls, but such an association among boys is controversial. Objective To estimate the association of prepubertal adiposity status, trajectories, and the earlier puberty onset based on a cohort study. Design, Setting, and Participants A total of 1322 children were included in 2017, with a mean age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In addition, obesity may constitute a chronic stressor and in turn impair brain functions involved in affective control, by inducing chronic inflammation, dysfunctions in the hypothalamic–pituitary–adrenal axis [31], and dysregulations of adipokines [33]. In line with previous findings [25, 34], our study also found that girls with the trajectory of increasing adiposity had earlier menarche ages and menarche age was associated with BMI/WHtR trajectories, which may suggest a risk of the metabolic‐reproductive interplay among female adolescents with early menarche ages involving adipokines (leptin and ghrelin), hormones (insulin), and lipid, as well as critical signaling pathways (AMPK/SIRT, mTOR) that may integrate the peripheral metabolism and central circuits [35]. Furthermore, the associations between the “rapidly increasing” BMI z score/WHtR trajectory and subsequent neurobehavioral deficits remained significant when taking pubertal timing into consideration (additionally adjusting for menarche age in girls), indicating that rapidly increasing adiposity or abdominal obesity from ages 11 to 15 years may be an independent risk factor for neurobehavioral deficits among female adolescents.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, obesity may constitute a chronic stressor and in turn impair brain functions involved in affective control, by inducing chronic inflammation, dysfunctions in the hypothalamic–pituitary–adrenal axis [31], and dysregulations of adipokines [33]. In line with previous findings [25, 34], our study also found that girls with the trajectory of increasing adiposity had earlier menarche ages and menarche age was associated with BMI/WHtR trajectories, which may suggest a risk of the metabolic‐reproductive interplay among female adolescents with early menarche ages involving adipokines (leptin and ghrelin), hormones (insulin), and lipid, as well as critical signaling pathways (AMPK/SIRT, mTOR) that may integrate the peripheral metabolism and central circuits [35]. Furthermore, the associations between the “rapidly increasing” BMI z score/WHtR trajectory and subsequent neurobehavioral deficits remained significant when taking pubertal timing into consideration (additionally adjusting for menarche age in girls), indicating that rapidly increasing adiposity or abdominal obesity from ages 11 to 15 years may be an independent risk factor for neurobehavioral deficits among female adolescents.…”
Section: Discussionsupporting
confidence: 88%
“…Yanhui et al. have also recently showed an association between prepubertal adiposity and earlier puberty onset both in females and in males ( 35 ).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies found that the values of weight, height, WC (33), BMI, and WHtR (32) in precocious puberty children were higher than those in peer normal children. Children with high-level of body fat as well as those with a rapid increase in anthropometric profiles were more sensitive to earlier puberty onset (24) (25). However, based on the relatively small number of studies available, more findings about the effect of fat distribution on pubertal development in girls should be done in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the values of weight, height, WC ( 33 ), BMI, and WHtR ( 32 ) in precocious puberty children were higher than those in peer normal children. Children with high-level of body fat as well as those with a rapid increase in anthropometric profiles were more sensitive to earlier puberty onset ( 24 ). Our results, together with data reported by others, indicated the importance to maintain healthy adiposity status in preventing earlier puberty onset in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation